IFN‐γ orchestrates tumor elimination, tumor dormancy, tumor escape, and progression. Issue 6 (22nd February 2018) - Aqbi, Hussein F.; Wallace, Matthew; Sappal, Samay; Payne, Kyle K.; Manjili, Masoud H.
Abstract: Tumor immunoediting consisting of three phases of elimination, equilibrium or dormancy, and escape has been supported by preclinical and clinical data. A comprehensive understanding of the molecular mechanisms by which antitumor immune responses regulate these three phases are important for developing highly tailored immunotherapeutics that can control cancer. To this end, IFN‐γ produced by Th1 cells, cytotoxic T cells, NK cells, and NKT cells is a pleiotropic cytokine that is involved in all three phases of tumor immunoediting, as well as during inflammation‐mediated tumorigenesis processes. This essay presents a review of literature and suggests that overcoming tumor escape is feasible by driving tumor cells into a state of quiescent but not indolent dormancy in order for IFN‐γ‐producing tumor‐specific T cells to prevent tumor relapse. Abstract : Review on the mechanisms by which IFN‐gamma manifests paradoxical functions of relevance to developing highly tailored immunotherapeutics for cancer patients.